Enhancement of Gas Separation performance of Carbon Nanotubes Mixed Matrix Membranes with Acid and Alkali Treatment - Nor Emma Erwina, Wahab; C. K. M., Faizal (2013)

(untitled)
Carbon nanotubes have special properties according to the different diameter, length, and direction of 'twist' of the nanotubes.